2007
DOI: 10.1080/00288250709509745
|View full text |Cite
|
Sign up to set email alerts
|

Mikronegeria fuchsiaesp. nov., a rust fungus onFuchsiaandPhyllocladusin New Zealand

Abstract: inoculations showed that two previously described rust fungi (Basidiomycota: Pucciniales), Caeoma peltatum on Phyllocladus spp. and Uredo fuchsiae on Fuchsia spp., both endemic to New Zealand, are different stages of a single species. Uredinial and telial states formed on Fuchsia excorticata after inoculation with aeciospores from Phyllocladus trichomanoides. The oblong teliospores form directly from subepidermal hyphae, then divide to become metabasidia, each cell of which germinates to form a long suprastoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…An evolutionary origin of rust fungi on angiosperms was supported by Aime (), who showed that some extant species, including H. vastatrix (on Rubiaceae), Blastospora smilacis (on Smilacaceae) and Maravalia cryptostegiae (on Apocynaceae), belonged to an ancestral family, Mikronegeriaceae (Pucciniales). This family is typified by Mikronegeria , which is heteroecious on gymnosperms and Nothofagus (Nothofagaceae, Fagales), or, in the case of M. fuchsiae , on a gymnosperm and Fuchsia (Onagraceae) (Crane & Peterson, ).…”
Section: Introductionmentioning
confidence: 99%
“…An evolutionary origin of rust fungi on angiosperms was supported by Aime (), who showed that some extant species, including H. vastatrix (on Rubiaceae), Blastospora smilacis (on Smilacaceae) and Maravalia cryptostegiae (on Apocynaceae), belonged to an ancestral family, Mikronegeriaceae (Pucciniales). This family is typified by Mikronegeria , which is heteroecious on gymnosperms and Nothofagus (Nothofagaceae, Fagales), or, in the case of M. fuchsiae , on a gymnosperm and Fuchsia (Onagraceae) (Crane & Peterson, ).…”
Section: Introductionmentioning
confidence: 99%
“…Its spermogonial and aecial stages are produced on Phyllocladus spp. (Crane and Peterson 2007). However, M. fuchsiae is quite different from P. epilobii in uredinial and telial morphology.…”
Section: Morphology Of Rust Fungus and Its Identificationmentioning
confidence: 88%
“…Crane et R. S. Peterson (0Uredo fuchsiae (Cooke) Henn, non Arthur et Holway) was reported to produce uredinial and telial stages on Fuchsia excorticata (J.R. Forst et G.) L.f. and F. perscandens Cockayne et Allan from New Zealand (Crane and Peterson 2007). Its spermogonial and aecial stages are produced on Phyllocladus spp.…”
Section: Morphology Of Rust Fungus and Its Identificationmentioning
confidence: 99%